COMPARISON OF THE MAIN CATCH AND BY-CATCH OF THE STOW NET BASED ON THE CAPTURE OF MAKING RESULTS TIME (HAULING) IN VILLAGE SIALANG PASUNG DISTRICT RANGSANG BARAT REGENCY OF MERANTI ISLANDS - Wita, Wirvina; Brown, Arthur; Nasution, Polaris (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRAK This research was conducted based on the tidal conditions that originated in the tidal tides of the Indonesian archipelago which were divided based on the highest tide conditions, average tide and lowest tide. In the village of Sialang Pasung, regency Meranti Islands. This study discusses the types of catches, studies and evaluates the main catch and by-catches of fishing gear based on differences of time. The method used in this study is the survey method, which is by fishing experiment in this researchlocation and making observations on two unit stow net (A and B)which operate in two methode namely four times hauling and two times hauling.The main catches of stow net A and B during the study were pepay(Mysis relicta) shrimp and Anchovy fish(Stolephorus indicus). While the by-catch are Mackerel fish(Cybium commersoni), Common hairtail(Trichiurus lepturus), Elongated llisha(Ilisha elongata), Bombay duck(Horpodon neherus), Dorab wolf-herring dorab(Chirocentrus dorab),Mullet(Valamugil engeli),Gangetic anchovy(Tryssa mystax), Spotted scat(Scatophagus argus),Vanname(Litopenaeus vannamei), Red prawn(Paneus monodon), Alphases shrimp(Alphases sp), Padachirus(Pardachirus pavonicus), White pomfret(Pampus argentus), Sagor catfish(Hexanematichthys sagor), and Squid(Loligo sp). The percentage main catches and by catches based on weight on stow net A and B is main catches is 45% and by catches is 55% based on individuals (tails) 94% main catches and 6% by catches.Keyword: Stow net, main catch, by-catches